Students' algebraic thinking: a study of mathematical modelling competencies. (April 2020) - Fakhrunisa, F; Hasanah, A
Abstract: Several components shows that the process of algebraic thinking on students in solving problems. One of these components is the process of using algebra as a tool for doing mathematical modelling. This study aims to reveal how the students' competency in making mathematical modelling for solving an algebraic problem. The descriptive qualitative study design was used to obtain an overview of the mathematical modelling competencies of nine students (15-16 years old) in Pekanbaru, Riau Province. Each participant received a test that contains an algebraic problem. The results of this study show that when students do mathematical modelling there are several errors as follows: (1) failure in making suppositions for the problem and simplifying the given situation; (2) failure in recognizing quantities that influence the given situation, to identify the key variable; (3) failure in construct relation between variable; and (4) failure in solving question within mathematical modelling.